Actinomyces infection of the mastoid: a rare entity - Subha, Sethu Thakachy; Raman, Rajagopalan; Cheah, Phaik Leng; Soon, Tuck Soo Hoo (Malaysian Medical Association, 2004)
A rare case of mastoid infection caused by actinomyces israelii is presented. This patient underwent exploratory mastoidectomy followed by long term oral pencillin. She responded well to the treatment and has been asymptomatic on follow up to date.